The Economic Burden of Clostridioides difficile in Denmark: A Retrospective Cohort Study - Braae, Uffe Christian; Møller, Frederik Trier; Ibsen, Rikke; Ethelberg, Steen; Kjellberg, Jakob; Mølbak, Kåre (Frontiers in Public Health, 2020)
Objectives The aim of this study was to make a comprehensive economic assessment of the costs of hospital-acquired C. difficile infections (CDI). Methods We carried out a retrospective matched cohort study utilising Danish registry data with national coverage to identify CDI cases and matched reference patients without CDI (controls) for economic burden assessment in Denmark covering 2011-2014. Health care costs and public transfer costs were obtained from national registries, and calculated for one year prior to, and two years after index admission using descriptive statistics and regression analysis. Results The study included 12,768 CDI patients and 23,272 matched controls. The total health care cost was significantly larger for CDI cases than controls throughout all periods. During the index admission period, cost was €12,867 per CDI case compared to €4,522 (p<0.001) for controls, which increased to an average of €31,388 and €19,512 (p<0.001) in Year 1 for the two groups respectively. Excess costs were found both among infections with onset in hospitals and in the community. Diagnosis compatible with complications increased costs to on average >€91,000 per case. The regression analysis showed that CDI adds a substantial economic burden, but only explains about 1/3 of the crude difference observed in the matched analysis. Discussion The major economic impact of hospital-acquired CDI with complications underlines the importance of preventing complications in these patients. Our study provides an informed estimate of the potential economic per patient gain by successful intervention, which is likely to be relatively comparable across countries.